SERS study of different species of p-aminothiophenol adsorbed on silver nanoparticles - López-Ramírez, María Rosa; Ávila-Ferrer, Francisco José; Otero-Fernández-de-Molina, Juan Carlos; Soto-Martín, Juan (My University, 2018)
In the present work we have focused the discussion on the experimental and theoretical SERS spectra of the organic compound pATP recorded on silver colloids. The huge SERS of pATP on metal substrates is significantly different from its ordinary Raman spectra due to the formation of a new specie namely p,p’ –dimercaptoazobenzene (DMAB). The features of the SERS spectra of pATP are strongly dependent on many factors as i.e. the laser power density or the laser wavelength but there are still important aspects to understand as, for example, the effect of the concentration that has already been studied before by our group. In this case we have analyzed the effect of the concentration at different wavelengths on the SERS spectra of pATP on silver nanoparticles.
Keywords: Espectroscopía Raman; SERS; Nanoparticles; P-aminothiophenol